Evaluation of the hydrocarbon potential of the eastern for-caucasus and areas of possible localization hydrocarbon - Marina Anatolyevna Beituganova; Vladimir Alekseevich Gridin (Наука. Инновации. Технологии)
The territory of the Ciscaucasia is the oldest oil-producing region of Russia. Since the beginning of last century to the present throughout an intensive exploration, including seismic. The result is a dense network of seismic works mogt variety of details, which gave ample material for studying the deep structure of the various structural-tectonic elements and lithofacies composition of the rocks composing them, and spread on the area and also drilled thousands of deep wells, which allowed to estimate the character of the exposed sediments and their petroleum potential. In this article the comparative characteristic areas of the Eastern CIS-Caucasian oil and gas field, considered the allocation and delineation of structures and areas of possible localization of hydrocarbons, the estimation of the resource potential of hydrocarbon raw materials of oil and gas regions.